2016
DOI: 10.1161/atvbaha.115.307074
|View full text |Cite
|
Sign up to set email alerts
|

Platelet CD40 Exacerbates Atherosclerosis by Transcellular Activation of Endothelial Cells and Leukocytes

Abstract: Objective— Beyond their eminent role in hemostasis and thrombosis, platelets are recognized as mediators of inflammation. Platelet cluster of differentiation 40 (CD40) ligand (CD40L and CD154) plays a key role in mediating platelet-induced inflammation in atherosclerosis. CD40, the receptor for CD40L, is present on platelets; however, the role of CD40 on this cell type is until now undefined. Approach and Results— We found that in both mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 57 publications
3
80
0
2
Order By: Relevance
“…Interestingly, platelet:PMN aggregates formed during inflammation lead to SPM biosynthesis, which have been shown to reduce human platelet:PMN aggregates 119, 120 . Given that platelet:PMN aggregates contribute to plaque inflammation 121 , these results highlight that SPM may have additional protective roles in regulating PMN activation during inflammation associated with atherosclerosis.…”
Section: Cellular Actions Of Resolvins In the Context Of Cvdmentioning
confidence: 86%
“…Interestingly, platelet:PMN aggregates formed during inflammation lead to SPM biosynthesis, which have been shown to reduce human platelet:PMN aggregates 119, 120 . Given that platelet:PMN aggregates contribute to plaque inflammation 121 , these results highlight that SPM may have additional protective roles in regulating PMN activation during inflammation associated with atherosclerosis.…”
Section: Cellular Actions Of Resolvins In the Context Of Cvdmentioning
confidence: 86%
“…The CD40 is the receptor for CD40L, being present in platelets. Gerdes et al 17 have demonstrated in knockout mice for CD40 and ApoE that platelet plays a crucial role in inflammation by stimulating leukocyte and endothelial cells activation, thereby promoting atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet CD40 stimulates activations of leukocyte and endothelial cells and further promotes atherosclerosis [108]. Meanwhile, increased MMP-2 activity potentiates inflammation insults and plaque instability in the injured vascular wall [109].…”
Section: Effects Of S Miltiorrhiza and Its Isolated Compounds On Thementioning
confidence: 99%